Developing Students' Beginning Reading Textbooks With Inductive Model In Madrasah Ibtidaiyah - Khirjan Nahdi; Zuhrowardi YS; Asrihul Jannah; Nahdiyatun Nahdiyatun; Salahuddin Muhlis (Sumber Belajar Sejahtera, 2023)
The Research and Development (R&D) aims to 1) produce a practical beginning reading textbook with an inductive model that is easy-to-use and improves their reading skills pleasurably, 2) to develop a beginning reading textbook with an inductive model that is easy-to-use and to improve their reading skills pleasurably and 3) to determine effectiveness, validity, and practicality of the inductive model beginning reading textbook. MI NWDI 5 Pancor Rakam, Lombok Timur, was selected for study intention. The ADDIE model development comprises five phases: analysis, design, development, implementation, and evaluation. Data collection was applied for interviews, observations, questionnaires for material experts, questionnaires for linguists, questionnaires for media/design experts, teacher response questionnaires, and test-sheet-form. Trials in terms of product are carried out with limited-size trials and large-size trials. The Research and Development (R&D) retrieves a practical beginning reading textbook with an easy-to-use inductive model that improves their reading skills pleasurably. In addition, the material, language, and media/design were highly feasible for use in feasibility tests and teacher response assessments. Furthermore, such measures were concluded to be effective in use.